PENGARUH TEMPERATUR PADA PROSES PENCAIRAN BATUBARA BANKO SELATAN DAN YALLOURN - Yusnitati, Yusnitati; Hartiniati, Hartiniati (Badan Pengkajian dan Penerapan Teknologi, 2007)
A coal liqueafaction test was carried out to investigate the reactivity of an Indonesian brown coal, called South Banko, and an Australian brown coal, called Yallourn. Liquefaction was conducted to ascertain the effect of reaction temperature on thereactivity of both brown coals and it represents on the oil, CLB, CO+CO2 and C1 C4 yields. The result shows that South Banko coal is more reactive than Yallourn coal. South Banko coal gives a higher oil yield than that of Yallourn. Oil derived from SouthBanko coal increases as reaction temperature rises. In contrast, oil derived from Yallourn decreased as reaction temperature increased. This result indicated that South Banko has more labile structure than that of Yallourn and it can easily breakdown the structure of South Banko coal. In term of hydrocarbon gas, Yallourn produces higher yield than that of South Banko. This suggests that Yallourn coal has alkyl groups in its structure. It was also found that CO+CO2 yields are similar to both brown coals. South Banko has less CLB yield than that of Yallourn but the CLB yield of South Banko coal is higher than that of Yallourn while temperature is increased to 470oC. In short, the study shows that South Banko coal is more reactive than that of Yallourn coal and it is very potential for the coal liquefaction feedstock.